Penerapan Unsur Permufakatan Jahat Dalam Pasal 132 Ayat (1) Undang-Undang Republik Indonesia Nomor 35 Tentang Narkotika : Studi Putusan Pengadilan Negeri Medan Nomor : 2644/Pid.Sus/2017/Pn.Mdn - Gerry Anderson Gultom; Syafruddin Kalo; Muhammad Hamdan; Edi Yunara (USU LAW JOURNAL, 2019)
Abstract. The application of evil consensus elements in Article 132 paragraph (1) of the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics based on the decision of the Medan District Court Number: 2644 / Pid.Sus / 2017 / PN.Mdn on behalf of defendant Roni Sihombing and defendant Novrizal Batubara not in accordance with the full sound of Article 132 paragraph (1) of the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics, this can be seen clearly from the indictment, proof of elements by the public prosecutor in the judicial panel's decision and elemental verdict in the decision that omits the phrase "to do" in Article 132 paragraph (1) of the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics. The application of articles like this is clearly contrary to the law. The application of evil consensus elements in Article 132 paragraph (1) of the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics based on the decision of the Medan District Court Number: 2644 / Pid.Sus / 2017 / PN.Mdn on behalf of defendant Roni Sihombing and defendant Novrizal Batubara eliminating the phrase "to do" gives rise to different legal consequences of the intent and purpose of Article 132 paragraph (1) of the Law of the Republic of Indonesia Number 35 of 2009 concerning actual Narcotics. The phrase "to do" wants the perpetrators of crimes to be charged even though the criminal act has not been completed, but in this case the public prosecutor and the panel of judges actually prove the crime as referred to in the second indictment which has already been completed. By proving the second indictment, the public prosecutor and the panel of judges wasted the opportunity to prove the defendant's guilt in the first indictment, whose criminal threat was more severe even though the facts of the trial were very possible to prove the defendant's mistake in the first indictment. Keywords: application, elements, evil consensus, crime and narcotics.